ANALYSIS OF MARKETING MIX AND SALES PERFORMANCE OF “INDUSTRI HILIR TEH WALINI” PRODUCT - Dwi Oktaviyanti; Masyhuri Masyhuri; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
This research as a case study in “Industri Hilir Teh Walini” aimed to: (1) describe the marketing mix strategy, (2) examine the influence of marketing mix strategy on sales, (3) know the sales performance of products, (4) forecast the future demand of primary products, and (5) explore the strengths, weaknesses, opportunities, and threats (SWOT).Descriptive explanation, multiple linear regression analysis, one way analysis of variance, moving average forecasting, and SWOT analysis were conducted. This research showed that in the product mix as a component of marketing mix, this business unit offers tea products in various packaging and flavoring. The price determination conducted based on cost, market competition, and standards in certain lines. The promotion mix used are Above and Below The Line communication strategy. The place mix conducted by distributing products through selective distribution channel and direct channel. Promotion cost and flavor variants variables of the marketing mix were proven to have positive significant influence on the sales. Based on the one way analysis of variance, grouped tea product sales of tea bag, loose and instant tea, and ready to drink tea were significantly different. Forecast of black tea bag, lemon flavored black tea bag, and green tea bag sales volume in 2014 which give the best sales performance tend to be fluctuated. The SWOT analysis showed that this business unit’s position is in quadrant 1 which supports the SO (Strengths-Opportunities) strategy.